Comparison between the World Health Organization and Bahraini children growth standards - Shahzalan Almughlaq; Abdel-Ameer Al-Laith; Salwa Al-Thawadi (Revista Paulista de Pediatria, 2023)
Abstract Objective: The aim of this study was to investigate the growth patterns of Bahraini female and male infants/young children aged 0–24 months in the Kingdom of Bahrain. Methods: A cross-sectional approach was employed to track the growth parameters among healthy Bahraini female and male infants/children aged 0–24 months. A multistage probability sampling criteria was used to collect information from official records. Anthropometric measurements (weight and length) and demographic characteristics on feeding practices were gathered. Generalized Additive Models for Location Scale and Shape (GAMLSS)/Lambda-Mu-Sigma methodology was implemented to select distribution type, optimize smoothing parameters, perform regression of growth models, and construct percentiles and Z-score charts and tables for weight for age, length for age, length for weight, and body mass index (BMI) for age. Results: Findings were compared with WHO Multicentre Growth Reference Study (MGRS) data. A total of 403 healthy infants/children (210 males and 193 females) were recruited. At birth, the mean weight, length, and BMI were 3.2±0.4 kg, 3.1±0.4 kg, 49.7±2.3 cm, 48.8±2.1 cm, 13.2±1.6 kg/m2, and 12.8±1.5 kg/m2 for males and females, respectively. Anthropometrics of males were all statistically significantly higher than those of females at all age levels. The length and weight of the Bahraini infants/children were slightly higher than those of the WHO-MGRS. Conclusion: The outcomes of this study, presented as charts and tables, showed significant differences in comparison with the WHO-MGRS reference charts. Specifically, Bahraini children aged between 0 and 24 months of both sexes were taller and heavier than their cohorts in the MGRS reference charts. Further longitudinal studies are needed for monitoring the growth pattern of children using body composition methods, adiposity markers, and determinant factors of growth to investigate this deviation from the WHO-MGRS.